2016
DOI: 10.1111/trf.13730
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of transfusion reactions: a multicenter study utilizing systematic active surveillance and expert adjudication

Abstract: Background Prevalence estimates of serious hazards of transfusion vary widely. We hypothesized that the current reporting infrastructure in the United States fails to capture many transfusion reactions, and undertook a multi-center study utilizing active surveillance, data review, and adjudication to test this hypothesis. Study Design and Methods A retrospective record review was completed for a random sample of 17% of all inpatient transfusion episodes over 6 months at 4 academic tertiary care hospitals, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
123
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 24 publications
8
123
1
2
Order By: Relevance
“…Such was noted in our study: even serious clinical signs—such as hypotension—that have been reported to be associated with STRs, were encountered in only a minority of cases. This finding is consistent with previous studies, which reported that vital signs are of limited utility in the recognition (or exclusion) of transfusion reactions . Similarly, prophylactic antibiotic therapy could mask signs and symptoms of sepsis as well as impede growth in blood cultures that are undertaken as part of the investigation of STRs .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such was noted in our study: even serious clinical signs—such as hypotension—that have been reported to be associated with STRs, were encountered in only a minority of cases. This finding is consistent with previous studies, which reported that vital signs are of limited utility in the recognition (or exclusion) of transfusion reactions . Similarly, prophylactic antibiotic therapy could mask signs and symptoms of sepsis as well as impede growth in blood cultures that are undertaken as part of the investigation of STRs .…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous studies, which reported that vital signs are of limited utility in the recognition (or exclusion) of transfusion reactions. 18,21 Similarly, prophylactic antibiotic therapy could mask signs and symptoms of sepsis as well as impede growth in blood cultures that are undertaken as part of the investigation of STRs. 22 Collectively, the reported symptoms and signs were shown to be inconsistent predictors of STRs and failed to discriminate BCPTRs and STRs reliably from other reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Our present study has provided strong clinical evidence of storage-associated PLT AEs with careful statistical analysis of a large sample size. A recent study showed that the reporting rate of most transfusion reactions ranged from 5% to 30% except for allergic reactions which were 50% at four tertiary academic hospitals in the United States [30]. Another study showed a similar reporting rate of 24% of all transfusion reactions types [31], with the self-reported AE rate of PLT transfusion of 0Á4% (0Á5% overall), which is similar to the overall AE rate of PLT transfusion in our current study (0Á56%).…”
Section: Discussionsupporting
confidence: 87%
“…In particular, severe cardiopulmonary complications, including transfusion‐related acute lung injury (TRALI) and transfusion‐associated circulatory overload (TACO), have been identified as the leading cause of transfusion‐associated death (Bolton‐Maggs et al, ). In a recent multicentre, retrospective analysis of almost 5000 transfusion episodes, 1·1% were associated with TACO and 0·08% with TRALI (Hendrickson et al, ). Other transfusion risks include anaphylaxis and hypotensive episodes and milder events, including febrile non‐haemolytic, minor allergic and delayed serological reactions.…”
Section: Efficacy and Safety Of Implementing Pbm In Surgerymentioning
confidence: 99%